Internship report and study concerning the threats and opportunities posed by additive manufacturing to moulding industry - Venkat, Anurag Ayyagari (2016)
This report will make a presentation and analysis of various parts and systems used in injection moulds for plastics. This review starts by explaining the injection moulding process of injection, followed by a description of mould standard parts and a process map of mould making. The report also comprises case studies regarding hybrid manufacturing methods of subtractive and additive manufacturing processes. A study regarding opportunities and threats posed by additive manufacturing to the moulding industry is also made in order to understand the future trends of plastic part production.